INOVASI PENGOLAHAN AIR BERSIH MENGGUNAKAN MODEL DYNAMIC GRAVEL FILTER DI DESA SIDOMULYO KECAMATAN AIR KUMBANG, BANYUASIN - Aprilyanti, Selvia; Faritzie, Hariman Al; Setiati, Tri Woro (Universitas Mataram, 2024)
Sidomulyo Village is a village in Air Kumbang District, Banyuasin. The problem of providing clean water in this area is that the clean water service distribution system has not been able to meet the water needs of all PDAM Sidomulyo Village customers which can only distribute water once every 2 days and the distribution of clean water is also hampered by power outages, so that water cannot be distributed which results in The need for clean water in Sidomulyo village has not been met. The availability of clean water sources for the community in Sidomulyo Village, Air Kumbang District, is currently only available from swamp water, well water and rainwater collected in ponds and water drums. The amount of rainwater is very limited and is not sufficient if it has to be used for all household needs. The limited supply of clean water to meet the needs of the community is the main obstacle experienced by residents in Sidomulyo Village. The implementation method consists of several stages, including Coordination with partners, Socialization, Training, Technology Application, Monitoring and Evaluation. Community service activities (PKM) in Clean Water Processing in Sidomulyo Village aim to: 1) increase knowledge about clean water and clean living culture, 2) provide technology skills for clean water processing processes. The results achieved are: 1) increased partner knowledge about the importance of clean water for health, 2) partners have knowledge and skills in dynamic gravel filter clean water processing for households.